Hydrogel Loaded with VEGF/TFEB‐Engineered Extracellular Vesicles for Rescuing Critical Limb Ischemia by a Dual‐Pathway Activation Strategy. Issue 5 (23rd July 2021) - Xing, Zheng; Zhao, Chen; Wu, Siwen; Yang, Depeng; Zhang, Chunchen; Wei, Xinbo; Wei, Xinran; Su, Haoran; Liu, Haifeng; Fan, Yubo
Abstract: Critical limb ischemia (CLI) is the most severe clinical manifestation of peripheral arterial disease, which causes many amputations and deaths. Conventional treatment strategies for CLI (e.g., stent implantation and vascular surgery) bring surgical risk, which are not suitable for each patient. Extracellular vesicles (EVs) can be a potential solution for CLI. Herein, vascular endothelial growth factor (VEGF; i.e., a crucial molecule related to angiogenesis) and transcription factor EB (TFEB; i.e., a pivotal regulator of autophagy) are chosen as the target gene to improve the bioactivity of EVs derived from endothelial cells. The VEGF/TFEB‐engineered EVs (Engineered‐EVs) are fabricated by genetically engineering the parent cells, and their versatile functions are confirmed using three cell models (human umbilical vein endothelial cells, myoblast, and monocytes). Injectable thermal‐responsive hydrogel are then combined with Engineered‐EVs to combat CLI. These results reveal that the hydrogel can enhance the stability of Engineered‐EVs in vivo and release EVs at different temperatures. Moreover, the results of animal studies indicate that Engineered‐EV/Hydrogel can significantly improve neovascularization, attenuate muscle injury, and recover limb function after CLI. Finally, mechanistic studies shed light on the therapeutic effect of Engineered‐EV/Hydrogel due to the activated VEGF/VEGFR pathway and autophagy‐lysosomal pathway. Abstract : The vascular endothelial growth factor (VEGF)/transcription factor EB (TFEB)‐engineered extracellular vesicles (Engineered‐EVs) are incorporated with injectable thermal‐responsive hydrogel. This Engineered‐EV/Hydrogel system can effectively improve neovascularization and attenuate muscle injury in the critical limb ischemia animal model. The activation of VEGF/VEGF receptor pathway and autophagy‐lysosomal pathway can be the potential therapeutic mechanism.